Investigation of the differences in volatile organic compounds of sesame oil under different processing methods using GC-IMS and electronic nose - Ai, Wen; Yin, Xinyi; Zhang, Shijia; Yu, Ziran; Liu, Yuqing; Huang, Dan (Frontiers in Nutrition, 2025)
IntroductionSesame oil is an edible oil of high economic and nutritional value, possessing a unique flavor and exerting various physiological effects, including antioxidant, anti-inflammatory, and hypoglycemic effects. Flavor compounds are essential in evaluating the taste and quality of food. To explore the impacts of water substitution method, cold-pressing method, and hot-pressing method on the volatile organic components and active aroma components of sesame oil.MethodsThis study employed the Heracles Neo ultra-fast gas-phase electronic nose and GC-IMS technology, combined with chemometric analysis, to analyze the volatile organic compounds (VOCs) of three groups of sesame oil samples.ResultsA total of 74 VOCs were detected in the three sesame oil samples, which were from GC-IMS and Heracles NEO ultra-fast gas-phase electronic nose (60 VOCs were detected via GC-IMS, 22 VOCs were detected via GC-IMS, among them, 8 VOCs were simultaneously detected via GC-IMS and Heracles NEO ultra-fast gas-phase electronic nose). The sesame oil produced via the water substitution method was rich in more than 42 VOCs, including Cyclopentanone, 1-Pentanol and had a more unique and richer flavor; the sesame oil produced via the cold-pressing method contains 4 VOCs, for example, γ -terpinene with an original fruity flavor; and the sesame oil processed by the hot-pressing method was rich in 29 VOCs, including 2-methyl-1-propanol, and had a better fat aroma.DiscussionThis study helps to improve the quality and flavor of sesame oil from the perspective of volatile components, facilitating technological innovation and industrial upgrades.